Application of Work-Life Balance in Banking: A Study Of Its Impact on Employee Well-Being - Silvy Sondari Gadzali (Return : Study of Management, Economic and Bussines, 2023)
Work-life balance is a policy and program that an organization or company can offer to workers to minimize the pressure and conflict of many roles when balancing career and family. Work-life balance itself is an important issue for now, balancing work time and personal life is a challenge that must be faced by the majority of employees who work in the banking industry. The purpose of this study is to analyze the impact of work-life balance implementation on employee welfare, including, job satisfaction, health, and personal life harmony. This research uses qualitative methods through literature review or documentation studies. Data is collected sourced from documents, books, journals, articles/other online media. The result of this study is the finding  of the impact of the implementation of work-life balance  in the banking industry which has an impact on employee welfare in terms of mental health able to reduce employee stress levels, physical health, career sustainability, financial health, community and social security.